LINGKUNGAN HIDUP DAN ALQURAN (Studi Deskriptif Multi-Pendekatan Ayat-ayat Alquran) - Yeni Rahman; Ihsan Nuzula (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2018)
Humans can not be separated from the environment, the environment is very meaningful for the survival of humans and other living things. Environment as a system, a system consists of components that work regularly as a unit. Searching the Koran's terms of the environment, through two approaches, namely the substance approach and the language approach. Of the two approaches, seven words connote the environment in the Koran. The seven words are al-ardh, al-balad, al-qaryah, al-alamin, al-sama ', al-biah, and jaww. Environmental preservation in the Koran is human being as part of the environment, humans as environmental users, and humans as holders of trust in maintaining the environment. The environmental preservation measures are to avoid environmental destruction, reduce lust, prioritize the afterlife than the world, approach political policies, realize the consequences of environmental destruction, maintain the cycle and availability of water, and increase garden and garden lands.